Sunni Suicide Attacks and Sectarian Violence. Issue 7 (2nd October 2020) - Choi, Seung-Whan; Acosta, Benjamin
ABSTRACT: Although fundamentalist Sunni Muslims have committed more than 85% of all suicide attacks, empirical research has yet to examine how internal sectarian conflicts in the Islamic world have fueled the most dangerous form of political violence. We contend that fundamentalist Sunni Muslims employ suicide attacks as a political tool in sectarian violence and this targeting dynamic marks a central facet of the phenomenon today. We conduct a large- n analysis, evaluating an original dataset of 6, 224 suicide attacks during the period of 1980 through 2016. A series of logistic regression analyses at the incidence level shows that, ceteris paribus, sectarian violence between Sunni Muslims and non-Sunni Muslims emerges as a substantive, significant, and positive predictor of suicide attacks. Indeed, the context of sectarian conflict predicts the use of suicide attacks to a much greater degree than the contexts of militant outbidding or foreign occupation. We also present five case examples, illustrating the use of suicide attacks in sectarian conflicts in Lebanon, Iraq, Syria, Nigeria, and Pakistan. Our overall results indicate that only a reduction in sectarian violence, and especially conflicts involving fundamentalist Sunni Muslims, can prevent the continuing spread of the suicide-attack phenomenon.